Frequency of Preterm Placental Abruption and its Contributing Factors - Zarrin Anwar, Urooj Anwar, Tehreem Khizar Malik, Saba Bajwa, Nida Dastageer, Safdar Nadeem Ch (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: The objectives of this study were to determine the frequency of preterm placental abruption in patients presenting with heavy bleeding in a tertiary care hospital and to determine the frequency of contributing factors towards preterm placental abruption. Methodology: This was a descriptive case series conducted at Department of Obstetrics & Gynecology at Allama Iqbal Memorial Teaching Hospital, Sialkot. This study involved 260 women aged between 20-40 years who presented with heavy vaginal bleeding between 32-37 weeks of gestation. Preterm placental abruption was noted and contributing factors namely Dai handling, chronic hypertension, premature rupture of membranes, grand multi parity, and maternal age more than 35 years were looked for. A written informed consent was taken from each patient. Results: The age of the patients ranged from 20 years to 40 years with a mean of 29.78±6.07 years. The gestational age of the patients ranged from 32 weeks to 37 weeks with a mean of 34.40±1.68 weeks. BMI of the patients ranged from 21.1 Kg/m2 to 35.8 Kg/m2 with a mean of 28.03±4.15 Kg/m2. Preterm placental abruption was noted in 12 (4.6%) patients. There was no significant difference in the frequency of placental abruption across gestational age (p=0.913) and BMI (p=0.958) of the patient. Among the contributing factors Dai handling was noted in 58.3% patients with preterm placental abruption followed by maternal age > 35 years (33.3%) and premature rupture of membranes and grand multiparity which were observed in 25.0% patients each. Chronic hypertension was recorded in 16.7% patients. There was no significant difference in the frequency of these contributing factors across gestational age and BMI of the patient. Conclusion: The frequency of preterm placental abruption was found to be 4.6% with Dai handling (58.3%) and maternal age more than 35 years (33.3%) as the frequent contributing factors. Keywords: Preterm Placental Abruption, Contributing Factors, Dai Handling